(untitled) (Malden, MA, 2008)
This Handbook is an essential reference and a guide to the rapidly expanding field of Geographic Information Science : Designed for students and researchers who want an in-depth treatment of the subject, including background information; Comprises around 40 substantial essays, each written by a recognized expert in a particular area; Covers the full spectrum of research in GIS; Surveys the increasing number of applications of GIS Predicts how GIS is likely to evolve in the near future
Keywords: Geography,Geographic information systems,Hệ thống thông tin địa lý,Địa lý; Data processing,Xử lý dữ liệu